OPTIMIZATION OF HYDROCARBON INFLOW USING CUMULATIVE PERFORATORS IN THE BAZALIIVSKA AREA - Chernyshov D. V. (НТУ «ДП», 2024)
The Bazaliivska area, a significant hydrocarbon field, has been the site of various experiments aimed at optimizing hydrocarbon extraction techniques. Recent studies have focused on cumulative perforators, particularly PNKT perforators, to determine how changes in perforation density, shot depth, and well pressure affect hydrocarbon inflow rates . The efficiency of these perforators was assessed by analyzing the inflow rates and comparing them across varying test conditions to identify optimal parameters. This study examines the results from these experiments, highlighting the potential of PNKT perforators to improve hydrocarbon inflow and providing insights into optimal operational settings.
Keywords: Bazaliivska area; experiments